Design analysis of unbraced frame using ANSYS - Farhana, Abdul Halim (2010)
Recently, the application of unbraced steel frame in building construction arises rapidly nowadays, various researches has been carried out to study the behavior of this type of frame. The tested frame structure was designed using available recommendation in the existing literature. Finite Element Analysis is devejoped to stimulate unbraced frame's deflection behavior. The result is compared with the range of value of several goodness-of-fit measures which are provided from random output parameter in each response surface set. Polynomial mathematical model generated using various combination parameters using multiple regression analysis were found to be statistically significant. Parametric study using response surface methodology through finite element analysis may form efficient approximation to immediate deflection. It shows a comparable result and thus, this program is expected applicable.